A comparative surface evaluation of orthodontic mini-implants before and after en masse retraction-A SEM study - Alok Ranjan; Pravin Shetty; Rahul Despande; Anil Biradar; Waseem Khan; Rohit Kulshrestha (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVE: To evaluate the changes in surface morphology of two different types of mini-implants after clinical en masse retraction using scanning electron microscopy. MATERIAL AND METHODS: Fifty mini-implants of Dentos (Korea, Absoanchor, BH-1817-08) and Orlus (Korea, Yesanchor, C-1817) were inserted in patients in a split-mouth design who required en masse anterior retraction and absolute anchorage. Surface characteristics of mini-implants such as pitch (distance between consecutive threads), flank width (distance between root and crest), and taper were studied using scanning electron microscope (FEI nanosem450) before and after clinical use. RESULTS: Statistically significant difference (p value = 0.003) was found in a mean reduction of pitch dimension among the two groups with a mean difference of 25.000 μm. Also, a statistically significant difference was noted (p value = 0.001) in a mean reduction of flank width among Dentos implants as compared to Orlus implants. A statistically significant difference (p = 0.001) was seen in the mean reduction of taper dimension among Dentos group (0.0140 ± 0.02271) as compared to the Orlus group (0.0810 ± 0.05152). CONCLUSION: A marked reduction in surface morphology such as the pitch, flank width, and taper of both mini-implants after retrieval was observed. Dentos group of mini-implants displayed better dimensional stability post-retrieval as compared to the Orlus group of mini-implants. All the mini-screws showed milling defects in form of scratches on observation under scanning electron microscopy despite a smooth appearance to the naked eye.